Peran Peradilan Militer Dalam Menegakkan Disiplin dan Hukum di Lingkungan TNI - Amalia, Firda; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Military courts play a strategic role in maintaining discipline, stability, and legal enforcement within the Indonesian National Armed Forces (TNI). Any violation committed by TNI personnel can seriously impact the institution's reputation, troop morale, and public trust in the rule of law. This study examines how military courts function as a legal instrument in handling disciplinary violations and military crimes, as well as evaluates their effectiveness in upholding justice and preserving military hierarchy. The analysis is conducted using a normative juridical approach by reviewing legal instruments such as Law No. 31 of 1997 on Military Justice and Law No. 25 of 2014 on Military Discipline Law. The findings indicate that although the military justice system has a clear and structured legal mechanism, it still faces challenges in terms of transparency, accountability, and the independence of military judges.